Effect of premedication on hemodynamics and bispectral index in pediatric dental rehabilitation - Elif Sungurtekin Ekci (Cumhuriyet University, 2016)
Objectives: The aim of this study was to evaluate the effects of rectal midazolam premedicationon hemodynamic parameters and Bispectral Index Scale (BIS) values in children undergoinggeneral anesthesia (GA) for dental rehabilitation.Materials and Methods: Records of 30 children aged 2 to 7 years were retrieved and dividedinto 2 groups. Group 1 received midazolam 0.3mg/kg body weight rectally and group 2involved children who did not receive any presedative (control). Mean arterial blood pressure(MAP), heart rate (HR), oxygen saturation (SpO2), and BIS were evaluated for six times; beforelaryngoscopy(1); 1 min(2); 5 min(3); 10 min after nasotracheal intubation(4); at the time ofextubation (5) and at the time of recovery(6). Paired t-test was performed to analyze all data.p<0.05 was defined as statistically significant.Results: MAP and HR did not differ significantly between both groups before laryngoscopy(p>0.05) but increased significantly in control group 1 min after intubation (p<0.04). SpO2was in the normal range in both groups, which was statistically insignificant (p>0.05). The BISrecords of the midazolam group were slightly lower than the control group in general but thisdifference was insignificant (p>0.05).Conclusions: Midazolam premedication prior to GA induction resulted with lower MAP and HRthan the control group 1 minute after intubation whereas it did not alter BIS values remarkablyat all time intervals. Therefore, the midazolam sedation did not produce a significant change inreducing GA awareness in children undergoing GA for dental rehabilitation.